Circuit Training Improvements in Korean Women with Sarcopenia. Issue 5 (October 2019) - Jung, Won-Sang; Kim, Yae-Young; Park, Hun-Young
Sarcopenia is defined as an age-related decrease in muscle mass, strength, and function. We investigated the effect of circuit training on body composition, balance, muscle mass and strength, and pulmonary function in Korean women with sarcopenia. We randomly assigned 26 Korean women with sarcopenia ( M age  = 74.9, SD =  4.5 years) to either an exercise group (EG) ( n  = 13) or a control group (CG) ( n  = 13). The EG performed 25-75 minutes of circuit exercise training (gradually increasing time periods) three times per week over 12 weeks, while the CG maintained their usual daily lifestyle during the intervention period. We measured body weight, body mass index, percent body fat, free fat mass, balance ability, peak torque in shoulder, knee, and lumbar joints normalized for bodyweight (BW), forced vital capacity, percentage of forced expiratory volume in one second, and forced expiratory flow 25–75% before and after the intervention. The EG showed improved body composition (i.e., body mass index, fat-free body mass, fat mass; all p  < .032, η 2  > 0.180), balance (i.e., right and left of static and dynamic balance and fast 10-m walk; all p  < .050, η 2  > 0.151), muscular function (i.e., 90°/s and 180°/s peak power per kilogram BW, 90°/s average power per kilogram BW, 180°/s total work, and 180°/s endurance ratio; all p  < .045, η 2  > 0.157), and pulmonary function (all p  < .005, η 2  > 0.292). On the other hand, the CG showed no significant changes. Circuit exercise training improves muscle mass and strength, body composition, balance, and pulmonary function in women with sarcopenia.